Constitution without Constitutionalism? Challenges to constitutionalism in the Kyrgyz Republic - Saniia Toktogazieva (The Constitutional Court of the Republic of Indonesia, 2019)
Application of basic principles revolving around the constitutionalism into third wave democracies, produced such phenomenon as constitutions “without constitutionalism”. This paper will revisit and discuss this issue in the context of the Kyrgyz Republic. Main argument and thesis of the paper is following: Where a viable balance of power exists, a constitutional court acquires importance as a key element of that order, thus promoting the constitutionalism. If no such balance exists, the constitutional court will soon become a tool of the more dominant powers and thus lose its relevance for a genuine constitutional order. The abovementioned thesis will be demonstrated by the example of the work of Constitutional Court of the Kyrgyz Republic. Mainly it first aims at providing a proper foundation and basic understanding of constitutionalism, further revisiting this concept in the context of Former Soviet Union and finally will discuss the development of constitutionalism in Kyrgyzstan along with challenges faced by the court.